PENINGKATAN KETERAMPILAN MENULIS CERITA MELALUI TEKNIK TIRU MODEL SISWA KELAS III SD NEGERI 200208 PADANGSIDIMPUAN - Rosyidah .; Syahrul R; Ermanto . (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: The objectives of this study are to describe of the process of improvement the writing skill to write stories and describe the resulting increase in the skill of writing a children's story-assisted film